Implementasi Kebijakan Pengawasan Pelaksana Penempatan Tenaga Kerja Indonesia Swasta (PPTKIS) di Dinas Tenaga Kerja dan Transmigrasi Provinsi Banten (Studi Pada Kabupaten Serang) - Nia Suganda; Arif Nugroho; Rahmi Mulyasih (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2020)
This study aims to find out how the Implementation of the Implementation Policy for the Implementation of Private Indonesian Manpower Placement (PPTKIS) in the Banten Province Manpower and Transmigration Office (Study in Serang District) and what are the supporting and inhibiting factors in supervising the Supervision of the Implementation of Private Indonesian Manpower Placement ( PPTKIS) in the Banten Province Manpower and Transmigration Office (Study in Serang District). In this study using descriptive qualitative. With the research location in the Banten Province Manpower and Transmigration Office in Serang District Supervision, data collection techniques used interviews, observation, and documentation. This study uses the widodo theory (2018) 4 (four) public policy supervision factors, namely: (1) Actors controlling the implementation of policies, (2) Standard operating control procedures, (3) Financial resources and equipment, (4) Scheduling of Control Implementation. From the results of research using Widodo's theory (2018) Supervision on PPTKIS has not been running optimally because there is no synergy between internal control and external control actors, the agency also has no control schedule, the socialization is quite good but there are still complaints from the community.